Research on the impact of Beijing–Tianjin–Hebei electric power and thermal power industry on haze pollution - Jingkun Zhou; Ting Yin; Juan Tian (Energy Reports, 2022)
As one of the main reasons of haze pollution in Beijing–Tianjin–Hebei area, electric-power and thermal-power industry continues to increase its production scale and total energy consumption, which makes haze pollution in Beijing–Tianjin–Hebei area increasingly serious. Based on the exploration of the spatio-temporal variance map of electric-power and thermal-power industry in Beijing–Tianjin–Hebei area, the article selects pand data of 13 cities in Beijing–Tianjin–Hebei area from 2006–2019 and empirically tests the spatial effect of electric-power and thermal-power industry on haze pollution by using the measures of spatial autoregressive model (SAR) and spatial Durbin model (SDM). It was found that in the Beijing–Tianjin–Hebei area, the electric-power and thermal-power industry converges to Beijing, Tangshan and Tianjin, where high demand exists. The electric-power and thermal-power industry shows an overall trend of shifting to the east coast and south inland. Through SDM, it is found that the electric-power and thermal-power industry is an crucial source of haze pollution and has a significant spatial spillover effect. In response to the above phenomenon, it is suggested to improve the haze pollution in Beijing–Tianjin–Hebei area scientifically by improving the supply and distribution system, scientifically deploying power supply, scientifically planning the development of electric-power and thermal-power industry according to the environmental self-purification capacity, and scientifically improving technological innovation.